Seasonal variation of phytoplankton in Tuyen Lam reservoir in Da Lat, Vietnam - Tinh, Tran Thi; Hai, Doan Nhu; Dung, Le Ba (Academia Journal of Biology, 2016)
Seasonal variation and phytoplankton dynamics in Tuyen Lam reservoir in Da Lat city, Viet Nam were studied in the rainy and dry seasons (during January through December, 2014). Samples were taken monthly from 3 stations of Tuyen Lam reservoir. The aim of this study was to analyze the structure of the phytoplankton community on seasonal scales and to identify the environmental factors, such as temperature, conductivity, pH, dissolved oxygen, light intensity, transparency, ammonium, nitrate and phosphate controlling the phytoplankton density and composition of phytoplankton communities. The results showed that phytoplankton comprised 43 taxa, mainly Chlorophyta (58%), Bacillariophyta (14%), Cyanobacteria (14%), Dinophyta (7%), Chrysophyta (5%) and Euglenophyta (2%). There was significant difference in phytoplankton abundance but not species richness between two seasons. Multiple regression analysis between chlorophyll a contents, phytoplankton density with environmental independent variables indicated that ammonium, nitrate concentrations and water temperature were significantly impact to the abundance of phytoplankton, while almost no independent variables were found to correlate to chlorophyll a. CCA analysis phytoplankton and abiotic parameters revealed several species groups with their favorable environmental conditions.